Association between 25-Hydroxyvitamin D and Metabolic Syndrome in Older Adults: The Health, Aging and Body Composition Study - Subhashish Agarwal; Janet A. Tooze; Douglas C. Bauer; Jane A. Cauley; Tamara B. Harris; Annemarie Koster; Catherine R. Womack; Stephen B. Kritchevsky; Denise K. Houston (International Journal of Endocrinology)
Objective. Low 25-hydroxyvitamin D (25[OH]D) levels and metabolic syndrome (MetS) are prevalent among older adults; however, longitudinal studies examining 25(OH)D status and MetS are lacking. We explore the association of 25(OH)D levels with prevalent and incident MetS in white and black older adults. Research Design and Methods. A total of 1620 white and 1016 black participants aged 70–79 years from the Health ABC cohort with measured 25(OH)D levels and data on MetS and covariates of interest were examined. The association between 25(OH)D levels and prevalent MetS at baseline and incident MetS at 6-year follow-up was examined in whites and blacks separately using logistic regression adjusting for demographics, lifestyle factors, and renal function. Results. At baseline, 635 (39%) white and 363 (36%) black participants had prevalent MetS. In whites, low 25(OH)D levels were associated with prevalent MetS (adjusted OR (95% CI), 1.85 (1.47, 2.34)) and 1.96 (1.46, 2.63) for 25(OH)D of 20–<30 and <20 vs. ≥30 ng/ml, respectively). The association was attenuated after adjustment for BMI but remained significant. No association was found between 25(OH)D levels and prevalent MetS in blacks. Among those without MetS at baseline (765 whites, 427 blacks), 150 (20%) whites and 87 (20%) blacks had developed MetS at 6-year follow-up. However, 25(OH)D levels were not associated with incident MetS in whites or blacks. Conclusion. In older adults, low 25(OH)D levels were associated with increased odds of prevalent MetS in whites but not in blacks. No association was observed between 25(OH)D levels and incident MetS in either whites or blacks.